Effect of mercury exposure on the growth and physiological characteristics of lowland tomato (Solanum lycopersicum) - Balachandran, Leethavani; Ahmad, Siti Aqlima; Mohd Amin, Adibah; Shaharuddin, Noor Azmi; Mohd Sobri, Mohamad Zulfazli; Mohamad Azzeme, Azzreena (Hibiscus Publisher Enterprise, 2024)
This study evaluates the effects of mercury (Hg) on tomato plants exposed to varying concentrations (0.01, 0.05, 0.10, and 0.25 ppm) for 14 and 30 days. Hg exposure led to significant reductions in plant height and leaf diameter, with more severe effects at higher concentrations. Notably, 0.01 ppm Hg caused increased branching and earlier ripening, whereas higher concentrations diminished flower and fruit counts, with 0.25 ppm Hg resulting in severe reductions and plant deterioration. Chlorophyll content was slightly higher at 0.01 and 0.05 ppm Hg but decreased at 0.10 and 0.25 ppm, indicating disrupted photosynthesis. Proline content, a stress marker, increased significantly in fruit and roots with higher Hg concentrations, peaking at 0.25 ppm. MDA levels, a marker of lipid peroxidation, increased with Hg concentration and duration, especially at higher levels. Visual symptoms of toxicity, such as wilting and chlorosis, were evident at 0.25 ppm Hg, indicating severe plant stress. The study highlights Hg adverse effects on tomato growth, morphology, and reproductive processes, with high concentrations causing severe toxicity and low concentrations having minor effects. Further research is needed to explore biochemical responses and establish Hg toxicity thresholds in tomato plants.